Cyclical etidronate increases bone density in the spine and hip of postmenopausal women receiving long term corticosteroid treatment. A double blind, randomised placebo controlled study. Issue 12 (1st December 1998) - Geusens, Piet; Dequeker, Jan; Vanhoof, Johan; Stalmans, Rita; Boonen, Steven; Joly, Jo; Nijs, Jos; Raus, Jef
Abstract : OBJECTIVE: To study the effect of cyclic etidronate in secondary prevention of corticosteroid induced osteoporosis. METHODS: A double blind, randomised placebo controlled study comparing cyclic etidronate and placebo during two years in 37 postmenopausal women receiving long term corticosteroid treatment, mainly for polymyalgia rheumatica (40% of the patients) and rheumatoid arthritis (30%). Bone density was measured in the lumbar spine, femoral neck, and femoral trochanter. RESULTS: After two years of treatment there was a significant difference between the groups in mean per cent change from baseline in bone density in the spine in favour of etidronate (p=0.003). The estimated treatment difference (mean (SD)) was 9.3 (2.1)%. Etidronate increased bone density in the spine (4.9 (2.1)%, p<0.05) whereas the placebo group lost bone (−2.4 (1.6)%). At the femoral neck there was an estimated difference of 5.3 (2.6)% between the groups (etidronate: 3.6 (1.4)%, p<0.05, placebo: −2.4 (2.1)%). The estimated difference at the trochanter was 8.2 (3.0) (etidronate: 9.0 (1.5)%, p<0.0001, placebo: 0.5 (2.3)%). No significant bone loss occurred in the hip in placebo treated patients. CONCLUSIONS: Cyclic etidronate is an effective treatment for postmenopausal women receiving corticosteroid treatment and is well tolerated.